On the problem of low-temperature ordering in ferro-antiferroelectric mixed compounds - Korynevskii, N.A.; Solovyan, V.B. (Condensed Matter Physics, 2009)
The problem of microscopic description of low-temperature phases in ferro-antiferroelectric mixed compounds
is discussed. Those phases (ferro-, antiferroelectric and dipole glass) are interpreted based on the specific
distributions for single and pair correlation functions in a non-ergodic thermodynamic system. Phase diagram
and dielectric susceptibility of a mixed system are obtained and analyzed. Обговорюється питання мiкроскопiчного опису низькотемпературних фаз у сегнето-антисегнетоелектричних змiшаних сполуках. Цi фази (сегнето-, антисегнетоелектрична i дипольного скла) iнтерпретуються на основi специфiчних розподiлiв для унарних i парних кореляцiйних функцiй в неергодичних термодинамiчних системах. Отримано i проаналiзовано фазову дiаграму та дiелектричну сприйнятливiсть змiшаної системи.